The Needs of Developing English Teacher’s Professional Competence In the 21st Century - Farouk Imam Arrasyid; Istiqomah (Ilmu Inovasi Nusantara, 2021)
The teacher's professional competence in the 21st century is required a great deal of knowledge, master the material critically, adapt to any changes in curriculum, master the technology, and solve problems encountered during the teaching process. Many researchers have already analyzed English teacher's needs toward professional competence in the 21st century. Here, there are presently several needs to develop an English teacher's professional competence into successful teaching and adjust the 21st century in more detail. This research strives to find the needs of developing English teacher's professional competence in the 21st century. The researcher employs a qualitative approach. The data were obtained through an interview with five professional English teachers’ competence. Then, the data were analyzed, interpreted, and presented using a narrative form. The result of interview analysis revealed that English teachers at Junior High School have indicated eighteen needs of developing professional competence in the 21st century, it required for the successful in teaching and learning. So, it can conclude that these needs greatly develop the professional quality of English teacher’s competence in teaching and carrying out the profession as English teachers